Competition, Innovation, and Inclusive Growth. (IMF Working Papers; Working Paper, 2021)
We provide an overview of the theories and empricial evidence on the complex relationship among innovation, competition, and inclusive growth. Competition and innovation-led growth are critical to drive productivity gains and support broad-based growth. However, new technologies and trends in market concentration are stifling future innovation while contributing to the marked increase in inequality. Beyond consumer welfare in a narrow market, competition policy should adapt to this new reality by considering the spillover and dynamic effects of market power, especially on firm entry, innovation, and inequality. Innovation policies should tackle not only government failures but also market failures.